Trends in the study of group support systems - Pervan, Graham; Arnott, David; Dodson, G. (University of Vienna, 2005)
This research project was principally motivated by a concern for the direction and relevance of DSS and GSS research. The main areas of research focus are the decision and judgement theoretic base of the discipline, the research strategies used in published articles, and the professional relevance of the research. The project has analysed 298 GSS articles published in 14 major journals from 1990 to 2003. The findings indicate that GSS research is more dominated by positivist research than general information systems; is most often published in the Journal of Group Decision and Negotiation; is poorly grounded in contemporary judgement and decision-making research; and falls down in the identification of the nature of clients and users. Of great concern is the finding that GSS research has relatively low professional relevance. An overview of the direction of further analysis is presented.